Resistance to first line anti-TB drugs by gene mutation and gene modulation - Louw, Gail Erika (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2009.